2002
DOI: 10.4049/jimmunol.168.7.3520
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Expression of Nuclear Cyclic Adenosine 5′-Monophospate Response Element-Binding Proteins and IFN-γ Promoter Function in Disease Due to an Intracellular Pathogen

Abstract: Mycobacterium tuberculosis-induced IFN-γ protein and mRNA expression have been shown to be reduced in tuberculosis patients, compared with healthy tuberculin reactors. To determine whether this decrease was associated with reduced activity of the IFN-γ promoter, we first studied binding of nuclear proteins to the radiolabeled proximal IFN-γ promoter (−71 to −40 bp), using EMSAs with nuclear extracts of freshly isolated peripheral blood T cells. Nuclear extracts of T cells from most tuberculosis patients showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 40 publications
3
31
0
Order By: Relevance
“…Some investigators found that CREB inhibited IFN-␥ transcription (31,55). In contrast, others found that CREB-enhanced IFN-␥ transcription (28,29), and reduced CREB expression, paralleled decreased IFN-␥ promoter activity in tuberculosis patients (29). In view of these findings, we determined whether CD40LT enhanced IFN-␥ production by M. tuberculosis-reactive CD8 ϩ T cells through the transcription factors CREB and AP-1.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Some investigators found that CREB inhibited IFN-␥ transcription (31,55). In contrast, others found that CREB-enhanced IFN-␥ transcription (28,29), and reduced CREB expression, paralleled decreased IFN-␥ promoter activity in tuberculosis patients (29). In view of these findings, we determined whether CD40LT enhanced IFN-␥ production by M. tuberculosis-reactive CD8 ϩ T cells through the transcription factors CREB and AP-1.…”
Section: Discussionmentioning
confidence: 95%
“…To investigate the mechanism for this effect, we studied transcription factors that bind the IFN-␥ promoter and enhance IFN-␥ mRNA expression in T cells. One of these transcription factors is CREB (28), and reduced CREB expression is associated with decreased IFN-␥ production in human tuberculosis (29). Phosphorylation of CREB enhances its capacity to up-regulate gene transcription (30) and we used Western blotting with a mAb specific for phosphorylated CREB to show that stimulation of CD8 ϩ T cells from three healthy donors with PMA and ionomycin enhanced phosphorylation of CREB within 15 min (Fig.…”
Section: Effect Of Cd40lt On Transcription Factors That Activate the mentioning
confidence: 99%
“…35 Genes whose transcription is regulated by CREB include those encoding the T helper type 1 (T H 1) cytokines. 61,62 The T H 1 cytokines encompass the cytokine profile of acute murine DSSinduced colitis (INF-␥, TNF-␣, and IL-1␤). 63 In T H 1 cells, the recruitment of phospho-CREB is significantly higher than in T H 2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 This may be ascribed to the þ 874 A/A genotype, 14 and also the reduced expression of nuclear cyclic adenosine 5 0 -monophosphate response element-binding protein and reduced IFN-g promoter activity in TB patients. 15 Moreover, IFN-g production from PBMCs is depressed in TB patients with A/A genotype when compared with A/T or T/T genotype at the time of diagnosis and after completion of treatment. 14 This suggests that A/A genotype may be related to TB severity or reactivation.…”
Section: Association Of Ifn-c and Il-10 With Tuberculosismentioning
confidence: 99%